2017
DOI: 10.1371/journal.pcbi.1005491
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcription factor resource sharing on gene expression noise

Abstract: Gene expression is intrinsically a stochastic (noisy) process with important implications for cellular functions. Deciphering the underlying mechanisms of gene expression noise remains one of the key challenges of regulatory biology. Theoretical models of transcription often incorporate the kinetics of how transcription factors (TFs) interact with a single promoter to impact gene expression noise. However, inside single cells multiple identical gene copies as well as additional binding sites can compete for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 101 publications
(94 reference statements)
1
25
1
Order By: Relevance
“…An important contributor to transcriptional noise is fluctuations in chromatin accessibility (Brown et al, 2013) and the limiting numbers of transcription factors. Single-cell chromatin accessibility measurements support the link between accessibility and transcriptional heterogeneity (Buenrostro et al, 2015), while mathematical modelling of the competition between genes for transcription factors revealed that this competition is sufficient to enhance mRNA copy number variability within an isogenic population (Das et al, 2017). Furthermore, pausing of RNA polymerase, a critical step during the initiation of transcription (Adelman and Lis, 2012) contributes to the stochasticity of gene expression.…”
Section: Sources Of Transcriptional Variabilitymentioning
confidence: 92%
“…An important contributor to transcriptional noise is fluctuations in chromatin accessibility (Brown et al, 2013) and the limiting numbers of transcription factors. Single-cell chromatin accessibility measurements support the link between accessibility and transcriptional heterogeneity (Buenrostro et al, 2015), while mathematical modelling of the competition between genes for transcription factors revealed that this competition is sufficient to enhance mRNA copy number variability within an isogenic population (Das et al, 2017). Furthermore, pausing of RNA polymerase, a critical step during the initiation of transcription (Adelman and Lis, 2012) contributes to the stochasticity of gene expression.…”
Section: Sources Of Transcriptional Variabilitymentioning
confidence: 92%
“…Binding competition can generate noise in two possible ways. First, TF binding is a dynamic process consisting of rapid binding and unbinding steps (Burger et al, 2010;Das et al, 2017). Thus, competition between TFs leads to a scenario where a gene is regulated by different subsets of TFs at different points of time, thus generating temporal variation in TF binding (Fig.…”
Section: Overlaps In Tf Binding Sites Lead To Higher Noisementioning
confidence: 99%
“…There is a history of using kinetic models to describe the dynamic processes of transcriptional regulation [19,20] In particular these models have been used to inform how the mean transcriptional levels and the variability around that mean depends on the dynamics of the processes that regulate transcription. This has culminated in a prevalent "On-off" model [14,19,[21][22][23][24][25][26][27][28] of promoter dynamics that considers initiation as being regulated by switching between a transcriptionally active and inactive state, the origin of this switching has been proposed as related to mechanisms such as transcription factor dynamics, chromatin accessibility or condensates of transcriptional machinery. This model has been extended to include the dynamics of the elongation process, to varying degrees; the roles of simple stochastic hopping, pausing and steric hindrance have all been considered and their contribution to phenomena such as traffic jams and transcription rate has been examined.…”
Section: Introductionmentioning
confidence: 99%